Preparation method of responsive multi-component material and application of responsive multi-component material in 129Xe / 1H dual-mode signal change
The 129Xe/1H dual-mode signal change is achieved through Fe3O4@SiO2@MnO2 multi-component material, which solves the problems of complex synthesis, low yield and poor biocompatibility of the existing 129Xe magnetic resonance contrast agent, and achieves high sensitivity and high specific hyperpolarization 129Xe magnetic resonance imaging, which significantly improves diagnostic accuracy.
Patent Information
- Application Number
- CN202411775467.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-05
AI Technical Summary
The existing 129Xe magnetic resonance contrast agents such as cage-shaped molecules and their derivatives have complex synthesis processes, low yields and poor biocompatibility, making it difficult to achieve high sensitivity and high specific hyperpolarization in vivo.
Fe3O4@SiO2@MnO2 is used as a responsive multi-component material to achieve 129Xe/1H dual-mode signal changes through interfering magnetic fields, enriching and developing hyperpolarized 129Xe magnetic resonance contrast agent.
The 129Xe/1H dual-mode imaging of the target substance in a specific disease environment has been achieved, which has significantly improved the accuracy of diagnosis. The synthesis process is simple, easy to modify and safe, and has great potential to diagnose specific diseases earlier and more accurately and monitor the occurrence and development of diseases.
Smart Images

Figure HDA0005171312060000011 
Figure HDA0005171312060000012 
Figure HDA0005171312060000013
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of nuclear magnetic resonance spectroscopy, and specifically relates to a method for preparing a responsive multi-component material and its application in 129 Xe / 1 H dual mode signal change application. Background Art
[0002] Magnetic resonance imaging (MRI) is a non-invasive imaging technique that can achieve high resolution and good tissue penetration, and plays an important role in the diagnosis and treatment of diseases. 1 H MRI uses protons in the water of a living body to image specific parts, which has low sensitivity and strong background interference. In order to improve the sensitivity of detection, enhanced MRI contrast agents can accelerate the proton relaxation process by changing the local magnetic field, thereby improving the sensitivity and diagnostic accuracy of MRI, but they are also limited by background signals. 129 Xe magnetic resonance imaging is a new imaging method that has emerged in recent years. 129 Xe MRI does not have background signal interference. And through spin exchange optical pumping technology, 129 Xe's magnetic resonance signal is enhanced by more than 60,000 times, thus enabling lung magnetic resonance imaging and obtaining information on lung structure and function for the evaluation of clinical lung diseases. 129 Xe itself is not specific, making it difficult to achieve specific detection of the target. 129 The researchers used direct magnetic resonance detection signals of Xe to specifically detect the target. They developed a caged molecule capture system modified with a targeting ligand. 129 Xe gas such as cryptand, cucurbituril, metal organic framework (MOF), etc. Among them, cryptand molecules and their derivatives are the most studied because they are related to 129 Xe has advantages such as good binding constant and easy modification of targeting ligands. However, the molecular synthesis process is complex and time-consuming, with low yield and poor biocompatibility, making it difficult to achieve in vivo application.
[0003] Fe 3 O 4 Nanoparticles have attracted much attention due to their outstanding advantages such as superparamagnetism, high specific surface area, low biotoxicity and flexible modifiability. The nanoparticles can accelerate the relaxation of protons by interfering with the magnetic field, thereby enhancing the MRI signal of protons. As an enhanced MRI contrast agent, Fe 3 O 4 Nanoparticles are usually designed as core-shell structures with a magnetic core and a shell made of various materials (such as polydopamine, MnO 2 、SiO 2The shell can not only make the chemical properties of the core more stable, but also realize the further functionalization of the particles (such as polydopamine, MnO 2 、SiO 2 and graphene, etc.) Among them, MnO 2 Nanoparticles have gradually become one of the most popular MRI contrast agent components due to their excellent biocompatibility, simple synthesis process, unique catalytic properties and magnetic resonance imaging properties. Duan et al. synthesized core-shell Fe 3 O 4 @C@MnO 2 Nanoprobes for pH-responsive T 1 / T 2 Dual-mode MRI contrast agent. Fe in acidic PBS at pH 5.0 3 O 4 @C@MnO 2 Nanoprobes can quickly release Mn 2+ , and with the help of superparamagnetic nanoparticles Fe 3 O 4 , while enhancing T 1 , T 2 Imaging. However, the diagnostic value of proton-based MRI is hampered by low signal intensity, which is mainly due to the low nuclear spin polarization of protons. Hyperpolarized MRI technology allows contrast agents to be detected with MRI signal intensities up to 5 orders of magnitude, with high detection sensitivity, but the use of this material for responsive hyperpolarized Xe MRI contrast agents has not yet been reported. Summary of the invention
[0004] For currently commonly used 129 Xe magnetic resonance contrast agents such as cage molecules and their derivatives have the disadvantages of complex synthesis, low yield and poor biocompatibility. The present invention provides a responsive multi-component material Fe 3 O 4 @SiO 2 @MnO 2 Preparation method and its 129 Xe / 1 H dual-mode signal changes. This material can cause 129 Xe / 1 H dual-mode signal changes, enriching and developing hyperpolarization 129 Xe magnetic resonance contrast agent, to achieve high sensitivity and high specificity hyperpolarization in vivo in the future 129 Laying the foundation for Xe magnetic resonance imaging.
[0005] In order to achieve the above-mentioned object of the present invention, the technical solution adopted by the present invention is:
[0006] A method for preparing a responsive multi-component material: The responsive multi-component material is Fe 3 O 4 @SiO 2 As a precursor, potassium permanganate is used as a raw material to prepare it. The specific steps are as follows: Fe 3 O 4 @SiO 2 The nanoparticles are uniformly dispersed in water, and then potassium permanganate solution is added to react; after the reaction is completed, the obtained precipitate is centrifuged, and the obtained precipitate is washed (preferably washed three times with deionized water) and vacuum dried to obtain a responsive multi-component material.
[0007] The responsive multi-component material obtained by the preparation method is a ternary composite material Fe with a core-shell-shell structure. 3 O 4 @SiO 2 @MnO 2 , with Fe 3 O 4 As the core, the core is wrapped with SiO 2 Shell, MnO 2 The outermost shell.
[0008] Furthermore, the Fe 3 O 4 @SiO 2 The nanoparticles are uniformly dispersed in water under ultrasound, the ultrasound power is 200 W, the ultrasound time is 3-10 min, and preferably, the ultrasound dispersion time is 5 min.
[0009] Furthermore, the Fe 3 O 4 @SiO 2 The mass ratio of nanoparticles to potassium permanganate is 1:0.8.
[0010] Furthermore, the reaction conditions are: the reaction temperature is room temperature, the reaction time is 6-10 hours, preferably, the reaction time is 8 hours.
[0011] Furthermore, the above centrifugation conditions are all centrifugation at 10000 r / min for 10 min.
[0012] Furthermore, the vacuum drying condition is as follows: drying in a vacuum drying oven at 50° C. for 24 hours.
[0013] The present invention also provides a method for preparing a responsive multi-component material obtained by the above preparation method. 129 Xe / 1 H dual mode signal change reagent application.
[0014] Furthermore, the application is: using the multi-component material as a hyperpolarizer 129 Xe magnetic resonance contrast agent.
[0015] This application discovered a Fe 3 O 4 @SiO 2 @MnO 2 Nanomaterials can interfere with the magnetic field and Fe 3 O 4 interaction, achieving 1 The magnetic resonance signal of H and 129 The change of dissolved state signal of Xe. In this nanomaterial, due to the MnO 2 The magnetic field shielding effect leads to 1 H's T 2 Magnetic resonance signal quenching, 129 The dissolved state signal of Xe is basically unchanged, but in certain disease environments (such as tumor microenvironment), MnO 2 Reduced to Mn 2+ , resulting in the proton's T 2 Signal recovery and 129 The image appears darker as the dissolved signal of Xe decreases. 3 O 4 @SiO 2 @MnO 2 Nanomaterials can be used as a multifunctional contrast agent to achieve 129 Xe / 1 H dual-mode imaging can significantly improve the accuracy of diagnosis and promote the development of multifunctional magnetic resonance nanoprobes. The synthesis process is simple, easy to modify and safe. In addition, the multifunctional material can cause changes in magnetic resonance signals according to changes in the level of GSH molecules in the disease, which can show abnormalities in the disease such as overexpression of GSH in tumor cells, which has great potential in diagnosing specific diseases earlier and more accurately and monitoring the occurrence and development of diseases.
[0016] Compared with the prior art, the beneficial effects and advantages of the present invention are:
[0017] 1. Compared with the traditional hyperpolarization based on cage molecules and their derivatives 129 Xe contrast agent, the contrast agent prepared by the present invention can achieve hyperpolarization by interfering with the magnetic field 129 The transformation of Xe magnetic resonance signal has the advantages of cheap raw materials, simple synthesis, easy modification and safety.
[0018] 2. The material of the present invention can realize the signal visualization transformation of specific disease marker molecules, which is different from the existing constant-brightness hyperpolarization 129Xe contrast agent. The contrast agent prepared by the present invention can link the specific changes of GSH in the disease with the changes of magnetic resonance signals, and can intuitively visualize the biochemical abnormalities in the disease, so that it can diagnose specific diseases earlier and more accurately and monitor the occurrence and development of the disease. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 is Fe in Example 1 3 O 4 , Fe 3 O 4 @SiO 2 , Fe 3 O 4 @SiO 2 @MnO 2 Transmission electron microscopy images of the materials;
[0020] Figure 2 is Fe in Example 1 3 O 4 @SiO 2 @MnO 2 Elemental distribution maps of multi-component materials;
[0021] Figure 3 Fe 3 O 4 @SiO 2 , Fe 3 O 4 @SiO 2 @MnO 2 , Fe 3 O 4 @SiO 2 @MnO 2 +10mM GSH solution system under the same conditions of the transverse relaxation rate of proton magnetic resonance signal changes;
[0022] Figure 4 Fe 3 O 4 @SiO 2 @MnO 2 and Fe 3 O 4 @SiO 2 @MnO 2 +10mM GSH solution system dissolved under the same conditions 129 Xe magnetic resonance signal change diagram. DETAILED DESCRIPTION
[0023] The applicant will now describe in detail the technical solution of the present invention in conjunction with specific embodiments.
[0024] The main reagents and instruments used in the following examples are as follows:
[0025] The reagents used in the following examples, sodium oleate, ferric chloride hexahydrate, polyoxyethylene (5) nonylphenyl ether (Igepal CO-520), tetraethyl silicate (TEOS), potassium permanganate, oleic acid, 1-octadecene were purchased from Aladdin Reagent Co., Ltd.; the reagents cyclohexane, anhydrous ethanol, and ammonium hydroxide (10M) were purchased from Sinopharm Chemical Reagent Co., Ltd. The nuclear magnetic resonance spectrometer model was 400MHz Bruker AV400 wide bore spectrometer.
[0026] Embodiment 1:
[0027] Fe 3 O 4 @SiO 2 @MnO 2 Preparation of multi-component materials
[0028] (1)Fe 3 O 4 Preparation of nanoparticles: Sodium oleate (30 mmol) and ferric chloride hexahydrate (10 mmol) were placed in a three-necked round-bottom flask, and then anhydrous ethanol (20 mL), ultrapure water (15 mL) and cyclohexane (35 mL) were added in sequence. The resulting mixture was refluxed at 70 ° C for 4 hours to obtain iron oleate. After that, the obtained iron oleate was dried in a vacuum oven (50 ° C, 48 h), and then dissolved in 1-octadecene (8 mL) and oleic acid (0.4 mL). The resulting mixture was transferred to a programmed temperature heating mantle, stirred under nitrogen atmosphere protection, heated to 200 ° C at a rate of 4 ° C per minute, and maintained at 200 ° C for 20 minutes. After the reaction was cooled to room temperature (25 ° C, the same below), 10 mL of anhydrous ethanol was added, centrifuged at a speed of 10,000 revolutions per minute for 10 minutes, and the precipitate was collected, and then centrifuged and washed three times with anhydrous ethanol again under the same conditions. The supernatant was discarded and dried in a vacuum oven at 50°C for 24 h. The obtained product was Fe 3 O 4 Nanoparticles.
[0029] (2)Fe 3 O 4 @SiO 2 Preparation of nanoparticles: Igepal CO-520 (0.25 mL) and the Fe 3 O 4Nanoparticles (0.75 mg) were dispersed in cyclohexane (5 mL) and stirred at room temperature for 15 min, then TEOS (1.2 μL) was added under stirring. After stirring for 30 min, a transparent, brown reverse microemulsion was formed. Then ammonium hydroxide (20 μL) was added and stirred at room temperature for another 18 h. After the reaction was completed, the precipitate was collected by centrifugation at 10,000 rpm for 10 min, then washed three times with anhydrous ethanol by centrifugation, and dried in a vacuum oven at 50 ° C for 24 h. The obtained product was Fe 3 O 4 @SiO 2 .
[0030] (3)Fe 3 O 4 @SiO 2 @MnO 2 Preparation of multi-component materials: Fe 3 O 4 @SiO 2 Dispersed in 10 mL ultrapure water (1 mg / mL), ultrasonicated for 10 minutes to make it evenly dispersed, then stirred at room temperature for 10 minutes, then added dropwise with 8 mL potassium permanganate aqueous solution (1 mg / mL) under stirring, and stirred at room temperature for 8 hours. After the reaction was completed, the precipitate was collected by centrifugation at a speed of 10,000 revolutions per minute for 10 minutes, the precipitate was washed twice with ultrapure water by centrifugation, and dried in a vacuum drying oven at 50°C for 24 hours to obtain Fe 3 O 4 @SiO 2 @MnO 2 .
[0031] Multi-component material Fe 3 O 4 @SiO 2 @MnO 2 Characterization
[0032] The Fe prepared in this example 3 O 4 , Fe 3 O 4 @SiO 2 , Fe 3 O 4 @SiO 2 @MnO 2 The material was characterized by transmission electron microscopy. 3 O 4 Nanoparticle TEM results are as follows Figure 1 As shown in (a), the Fe 3 O 4 @SiO 2 Nanoparticle TEM Figure 1As shown in (b), the Fe 3 O 4 @SiO 2 @MnO 2 Multi-component material TEM Figure 1 (c) shows that the prepared multi-component material has a spherical shape. Then, the multi-component material powder prepared in this embodiment is subjected to element mapping analysis. The obtained powder element map analysis results are shown in FIG. Figure 2 As shown, the presence of iron, silicon and manganese elements in the multi-component material is proved.
[0033] Example 2: Multi-component material Fe 3 O 4 @SiO 2 @MnO 2 exist 129 Xe / 1 H dual mode signal change test 1 Test steps for H proton signal changes
[0034] Take the dry multi-component material Fe prepared in Example 1 3 O 4 @SiO 2 @MnO 2 , add 1 mL of ultrapure water, and sonicate for 10 min at room temperature to fully disperse the multi-component materials in the aqueous solution to obtain a dispersion with an Fe concentration of 1.5 mM. The solution was then transferred to an NMR sample tube and the 1 / T 2 Value and get T 2 Weighted magnetic resonance image. Afterwards, in order to evaluate the responsiveness of the multi-component material to GSH, GSH was added to the above prepared solution to a concentration of 10 mM, ultrasonically mixed, and allowed to stand for 30 min. The solution was then transferred to an NMR sample tube and the sample 1 / T was recorded using the same parameter settings. 2 Value and get T 2 Weighted magnetic resonance image. For comparison, we used Fe prepared in Example 1 with the same Fe concentration of 1.5 mM. 3 O 4 @SiO 2 The nanoparticle material was dispersed in 1 mL of ultrapure water and ultrasonicated for 10 min at room temperature to make it uniformly dispersed. The dispersion was then transferred to the NMR sample tube and the sample 1 / T was recorded using the same parameter settings. 2 Value and get T 2 Weighted magnetic resonance image. The specific parameters are set as follows:
[0035] T 2Weighted imaging, repetition time (TR) = 2500 ms, echo time (TE) = 60 ms, slice thickness = 1 mm, slice spacing = 1 mm, FOV = 10 × 10 cm, matrix = 256 × 256;
[0036] T 2 Map imaging, TR=1000ms, TE=12-180ms, slice thickness=1mm, slice spacing=1mm, FOV=10×10cm, matrix=256×256.
[0037] Hyperpolarization 129 Xe signal change test steps
[0038] Take the dry multi-component material Fe prepared in Example 1 3 O 4 @SiO 2 @MnO 2 , added to 2 mL of ultrapure water, and ultrasonicated for 10 min at room temperature to fully disperse the multi-component materials in the aqueous solution to obtain a dispersion with an Fe concentration of 1.5 mM. The solution was then transferred to an NMR sample tube and recorded using a 400 MHz magnetic resonance imaging instrument. 129 Then, in order to evaluate the responsiveness of the multi-component material to GSH, GSH was added to the above prepared solution to a concentration of 10 mM, ultrasonically mixed, and left for 30 min. The solution was then transferred to the NMR sample tube and the sample was recorded using the same parameter settings. 129 Xe signal spectrum. For comparison, we tested 2mL of ultrapure water. 129 Signal spectrum of Xe. The specific parameter setting steps are as follows:
[0039] 129 Xe NMR experiments were performed on a 400 MHz (9.4 T) Bruker AV400 wide-aperture spectrometer (Bruker Biospin, Ettlingen, Germany) equipped with a micro-imaging gradient coil, with the RF pulse frequency of the Xe nuclei being 110.7 MHz. 129 Xe NMR spectroscopy using a 10 mm double resonance probe ( 129 Xe and 1 H, PABBO 400W1 / S2 BB-HD-10Z), rectangular pulses with flip angle (90°). Hyperpolarized light was generated by spin exchange optical pumping using a continuous flow polarization device. 129 Xe gas. The nuclear spin polarization is about 20%. By volume percentage 10% N 2 , 88% He and 2% Xe (Xe is 86% enriched129 Xe or natural abundance 129 Xe, the natural abundance used in this example 129 The mixed gas consisting of Xe) was directly passed into a 10 mm NMR tube for 20 seconds, and then waited for 3 seconds to ensure that the generated bubbles were completely broken before collecting the signal. The sample temperature was set to 300 K on the NMR spectrometer.
[0040] Experimental results:
[0041] Proton T 2 The results of the magnetic resonance signal test are as follows: Figure 3 As shown, from Figure 3 It can be seen that when the Fe concentration is the same, the multi-component material Fe 3 O 4 @SiO 2 @MnO 2 Proton transverse relaxation rate (1 / T 2 ) compared to Fe 3 O 4 @SiO 2 Correspondingly, T 2 Weighted imaging compared to Fe 3 O 4 @SiO 2 It is brighter, which is due to the MnO 2 The magnetic field shielding effect is caused by 3 O 4 @SiO 2 @MnO 2 When the solution reacts with GSH, due to the MnO 2 The redox reaction with GSH makes Fe 3 O 4 @SiO 2 Surface MnO 2 Splitting, so that 1 / T 2 Recovery, corresponding to T 2 The weighted image becomes darker. Similarly, the hyperpolarized 129 The Xe signal change test results are as follows Figure 4 As shown, due to MnO 2 The magnetic field shielding prevents Fe 3 O 4 Interacting with the magnetic field, Fe 3 O 4 @SiO 2 @MnO 2 Solution System 129 The intensity of Xe dissolved state signal is related to the pure aqueous solution 129 Xe has comparable strength. But when Fe 3 O 4@SiO 2 @MnO 2 When reacting with 10 mM GSH solution, GSH degrades MnO 2 The shell makes the exposed Fe 3 O 4 @SiO 2 The material interferes with the magnetic field, causing 129 The Xe signal is relaxed so that 129 The signal intensity of dissolved Xe decreased. This indicates that the multi-component material can be induced by the change of GSH. 129 Xe / 1 Changes in H dual-mode magnetic resonance signals can reveal abnormalities in diseases such as overexpression of GSH in tumor cells, making it possible to diagnose diseases earlier and more accurately, and to enrich and develop hyperpolarized 129 Xe magnetic resonance contrast agents are of great significance.
Claims
1. A method for preparing a responsive multi-component material, characterized in that: The responsive multi-component material is prepared using Fe3O4@SiO2 as a precursor and KMnO4 as a raw material, and the specific steps are: uniformly dispersing Fe3O4@SiO2 nanoparticles in water, then adding KMnO4 solution for reaction; centrifuging after the reaction, washing the obtained precipitate, and vacuum drying to obtain the responsive multi-component material.
2. The preparation method according to claim 1, characterized in that: The responsive multi-component material obtained by the preparation method is a ternary composite material with a core-shell-shell structure, with Fe3O4 as the core, a SiO2 shell layer wrapped outside the core, and MnO2 as the outermost shell layer.
3. The preparation method according to claim 1, characterized in that: The Fe3O4@SiO2 nanoparticles are uniformly dispersed in water under ultrasound, the ultrasound power is 200W, and the ultrasound time is 3-10 minutes.
4. The preparation method according to claim 1, characterized in that: The mass ratio of the Fe3O4@SiO2 nanoparticles to potassium permanganate is 1:0.
8.
5. The preparation method according to claim 1, characterized in that: The reaction conditions are as follows: the reaction temperature is room temperature, and the reaction time is 6-10 hours.
6. The preparation method according to claim 1, characterized in that: The centrifugation conditions are all at 10000 r / min for 10 min.
7. The preparation method according to claim 1, characterized in that: The vacuum drying condition is to dry in a vacuum drying oven at 50° C. for 24 h.
8. A responsive multi-component material obtained by the preparation method according to any one of claims 1 to 7 for preparing GSH responsive 129 Xe / 1 H dual mode signal change reagent application.
9. The use according to claim 8, characterized in that: The responsive multicomponent material is used as a hyperpolarizer 129 Xe magnetic resonance contrast agent.
Citation Information
Patent Citations
Application of metal organic framework nano contrast agent in ultra-sensitive magnetic resonance imaging
CN115400229A
Hyperpolarized 129Xe magnetic resonance molecular probe and preparation method thereof
CN116726208A
Microneedle patch loaded with multimode driving compound as well as preparation method and application of microneedle patch
CN116763714A
Non-spherical contrast agents for CEST MRI based on bulk magnetic susceptibility effect
EP2065058A1
A hyperpolarized contrast agent dispenser for magnetic resonance imaging
WO2010150209A1
Cited By
Preparation method of brown glass bottle
CN120622813A
Magnetic resonance imaging probe with 129Xe / 1H dual modes and preparation method and application thereof
CN122031725A